2004
DOI: 10.1111/j.0022-202x.2004.23478.x
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Enhances Early Healing After Cutaneous Incisional Wounding

Abstract: The epidermal growth factor receptor (EGFR) has been implicated in the regulation of wound healing. In order to directly evaluate the role of endogenous EGFR in cutaneous incisional wound healing, we examined EGFR null- and wild-type skin after injury. By 5 d after wounding, re-epithelialization was complete in all EGFR wild-type wounds, but in only 40% of EGFR null wounds. Delayed wound closure in EGFR null skin was accompanied by an increase in edema, longer lasting and more prominent eschar, and increased d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
107
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(116 citation statements)
references
References 19 publications
(30 reference statements)
6
107
0
Order By: Relevance
“…Galiano et al 30 demonstrated that pharmacological VEGF therapy in diabetics enhances neovascularization with a clinically significant effect. The mechanism for this effect is through a stimulation of local angiogenesis, enhanced expression of growth factors including PDGF and FGF-2, and a systemic mobilization of bone marrow-derived stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Galiano et al 30 demonstrated that pharmacological VEGF therapy in diabetics enhances neovascularization with a clinically significant effect. The mechanism for this effect is through a stimulation of local angiogenesis, enhanced expression of growth factors including PDGF and FGF-2, and a systemic mobilization of bone marrow-derived stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although other HER receptors participate in signaling, EGFR is the dominant EGF-family receptor in KCs, as evidenced by the severe impairment of wound reepithelialization observed in EGFR knockout mice. 26 EGFR is expressed throughout the epidermis, with its most prominent expression in the basal layer. 27 EGFR is activated in an autocrine manner by ligands synthesized by KCs, activated in a paracrine manner by ligands synthesized by platelets, lymphocytes, macrophages, or FBs, or transactivated by angiotensin II-or antimicrobial peptide hCAP18/LL-37-induced HB-EGF autocrine signaling.…”
Section: 21mentioning
confidence: 99%
“…EGFR therapy in conjunction with surgery must be considered very carefully as it is demonstrated that EGFR regulates multiple facets of wound healing, including inflammation, wound contraction, proliferation, migration and angiogenesis (Repertinger et al, 2004). In head and neck cancer, a small study with eight patients (Harari et al, 2003) receiving elective neck dissection after curative intended radiotherapy in combination with Cx, the length of hospital stay was not prolonged and no postoperative complications was found.…”
Section: Surgery and Antibody Therapymentioning
confidence: 99%